Efektivitas Penerapan E-Government dalam Mendukung Transparansi dan Keterbukaan Informasi Publik : Studi Kasus Website Resmi Dinas Komunikasi dan Informatika Kabupaten Lembata - Guido A. Ama Duli; Hendrik Toda; Delila A. Nahak Seran; Belandina Liliana Long (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effectiveness of the implementation of e-government in supporting transparency and public information disclosure on the official website of the Communication and Information Office of Lembata Regency. The type of research used is qualitative research with descriptive research methods. The number of informants in this study was 20 people using purposive sampling techniques. The results of this study use the theory of Sedar Maryanti (2009), namely input in the process of the effectiveness of the implementation of e-government in supporting transparency and disclosure of public information including various elements needed to ensure that the process of implementing e-government in supporting transparency and disclosure of public information runs smoothly and efficiently. In this case, including the quality of human resources, the number of workers, and also performance evaluation, the e-government system planning process at the Communication and Information Office of Lembata Regency has been running in a structured and gradual manner. This planning begins with mapping the available infrastructure, such as internet networks and other information technology devices. In addition, the approach used also considers the needs of digital services in all regions, including remote areas, the results (output) of the quantity of public information provided by the Communication and Information Office of Lembata Regency have been published quite regularly through the media from such as the official website and social media of the agency. The information presented includes local government activities, important announcements, and relevant reports.